Self-Expandable Metal Stenting of Refractory Upper Gut Corrosive Strictures: A New Role for Endoscopy? - Raffaele Manta; Rita Conigliaro; Helga Bertani; Mauro Manno; Ahmed Soliman; Paolo Fedeli; Gabrio Bassotti (Case Reports in Gastrointestinal Medicine)
Caustic strictures of the gastrointestinal tract are often difficult to treat, since relapses are frequent after medical or endoscopic treatment. Thus, novel approaches are needed. We report here our experience with self-expandable metallic stents (SEMS) as a new endoscopic approach in three patients with corrosive strictures of the upper gastrointestinal tract.